Awal Mula Bisnis Waralaba Amerika di Indonesia dan Perkembangannya Hingga Kini - Syaifullah, Handika; Angelina, Mesya; Santika, Lisa; Oktavia, Niken Wanda; Lestari, Nabila Mufti; Damanik, Pria Satria Sanjaya; Saragih, Jan Devit Dohardo (Medan Resource Center, 2024)
This research discusses the history, development, and influence of the American franchise business in Indonesia. The first American franchise to enter Indonesia was Kentucky Fried Chicken (KFC) in 1979, paving the way for many other American brands. This study uses a qualitative approach with literature review and in-depth interviews with industry players to obtain a comprehensive picture of the evolution of franchise businesses in Indonesia. The results show that American franchises have grown rapidly due to stable economic growth, an increasing middle class, and lifestyle changes favoring convenience. Government support through adequate regulations has also encouraged this growth. However, challenges such as intense competition, adaptation to local tastes, and regulatory issues persist. Despite these challenges, American franchises remain appealing due to their strong brand reputation and proven business systems. The research concludes that American franchises have significantly transformed and continue to play an important role in Indonesia's economy, with substantial potential for future growth.